2019
DOI: 10.32615/bp.2019.076
|View full text |Cite
|
Sign up to set email alerts
|

The intensity of and recovery from photoinhibition under drought in a thermotolerant common bean compared to drought tolerant genotypes

Abstract: The chlorophyll a fluorescence parameters of four Phaseolus vulgaris L. genotypes were evaluated under drought in two greenhouse experiments. Under severe water stress, the thermotolerant genotype 'Diplomata' maintained significantly higher values of predawn leaf water potential (Ψw), maximum Fv/Fm and effective (ΦPSII) quantum yield of photosystem II , and non-photochemical quenching than 'Ouro Negro', in the first experiment, and 'A 285' and 'A 222', in the second one. Among these parameters, Fv/Fm showed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A decrease in these values is related to the closure of the reaction centers and the processes of energy extinction in the form of heat [2]. According to Zlatev (2009) [5], when observing the behavior of wheat plants under drought, he concluded that photoinhibitory damage to PSII may be a secondary effect of drought [6]. This same study revealed that the Katia wheat variety showed greater tolerance to drought regarding photosynthetic activity since the Fv/Fm parameter remained high during the drought.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A decrease in these values is related to the closure of the reaction centers and the processes of energy extinction in the form of heat [2]. According to Zlatev (2009) [5], when observing the behavior of wheat plants under drought, he concluded that photoinhibitory damage to PSII may be a secondary effect of drought [6]. This same study revealed that the Katia wheat variety showed greater tolerance to drought regarding photosynthetic activity since the Fv/Fm parameter remained high during the drought.…”
Section: Introductionmentioning
confidence: 95%
“…Then, the difference between Fv/Fm after sunset minus Fv/Fm at dawn of the same day (day ∆Fv/Fm) and the difference between Fv/Fm at dawn minus Fv/Fm after sunset on the previous day (night ∆Fv/Fm) were evaluated [6]. The day ∆Fv/Fm was used to assess the effect of the photoinhibition during the day, and the night ∆Fv/Fm showed the capacity of recovery from the photoinhibition of the day before.…”
Section: Introductionmentioning
confidence: 99%
“…In the field, drought is generally associated with a high PPFD due to a clear sky, and photoinhibition an oxidative stress will occur even under moderate water stress, as shown in (Figure 1) [5]. Water deficit affects several physiological responses, varying in intensity among the species, its growth stages, and cultivation conditions [6].…”
Section: Mini-reviewmentioning
confidence: 99%
“…There is a reduction in A under mild water deficiency, but the causes of this reduction are still under debate. Some authors state that there is only a limitation of CO 2 substrate, a diffusional limitation due to stomatal closure under mild stress [5]. Nevertheless, at the onset of drought, there is stomata closure and a reduction of cell growth and protein synthesis and thus carbohydrate synthesis [6].…”
Section: Mini-reviewmentioning
confidence: 99%
See 1 more Smart Citation